Meaningful gamification: a conceptual model of discrete math in a blended classroom - Khalid, Nurkaliza; Zainuddin, Nor Zalina; Nuwairi, Nujaidah (Fakulti Sains & Teknologi Maklumat, Kolej Universiti Islam Antarabangsa Selangor, 2019)
Mathematics is embedded our lives in many ways. However, mathematics is often challenging for adult learners to master. The purpose of this paper is to identify problems encountered by the students after using gamification features implemented through Kahoot! questionnaires in a blended mathematic classroom. The gamification process in the study is based on Kevin Werbach’s framework for gamification. A qualitative research design using interviews was applied in this study to find out the students’ problems in learning after using Kahoot! questionnaires. Ten students were involved in the study and five major problems have been identified. Finally, the study proposed several gamification features to solve the mentioned problems. Future study will focus on implementing the proposed features and design a questionnaire to evaluate the feedback mechanism.